Positive electrode active material layer, electrode, and solid-state battery

By using vinylidene fluoride copolymer as the binder in the positive electrode active material layer, the problem of insufficient circulation characteristics in the prior art is solved, and excellent circulation characteristics of semi-solid state batteries or all-solid state batteries are achieved.

CN119631188APending Publication Date: 2025-03-14KUREHA CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380054623.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, although powders of specific elements are used as coating methods for conductive additives and active substances, the circulation characteristics have not been fully improved and there are durability problems.

Method used

The positive electrode active material layer is added as a binder. Specifically, the copolymer of vinylidene fluoride, hexafluoropropylene or chloroethylene trifluoroethylene ensures that the content of its structural unit is more than 83.0% and less than 97.0%.

Benefits of technology

By using vinylidene fluoride copolymer as the binder, the circulation characteristics of semi-solid state batteries or all-solid state batteries are significantly improved, so that the discharge capacity can reach 140 mAh/g or above after 50 cycles, and have excellent circulation characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247117950000131
    Figure BDA0005247117950000131
  • Figure BDA0005247117950000151
    Figure BDA0005247117950000151
Patent Text Reader

Abstract

Provided are: a positive electrode active material layer capable of forming an all-solid-state battery having excellent cycle characteristics; an electrode provided with the positive electrode active material layer; and a semi-solid-state battery or all-solid-state battery provided with the electrode. A positive electrode active material layer containing a positive electrode active material (A), a solid electrolyte (B), and a binder (C), the binder (C) containing a vinylidene fluoride copolymer, the vinylidene fluoride copolymer being a copolymer of vinylidene fluoride and hexafluoropropylene or a copolymer of vinylidene fluoride and chlorotrifluoroethylene, the vinylidene fluoride copolymer contains the structural units derived from vinylidene fluoride in an amount of from 83.0% by mass to 97.0% by mass (inclusive) when the total structural units of the vinylidene fluoride copolymer are 100.0% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode active material layer, an electrode and a solid-state battery. Background Art

[0002] In the previous secondary batteries containing electrolytes, when the battery cell is abnormal such as an internal short circuit of the battery cell or the temperature of the battery cell rises, the possibility of fire is extremely high. Therefore, from the perspective of improving the safety of the battery cell, research has been conducted on semi-solid batteries or all-solid batteries that convert most or all of the electrolyte into a solid electrolyte. Semi-solid batteries or all-solid batteries are considered to simplify safety devices and have excellent manufacturing costs and productivity because the electrolyte containing a flammable organic solvent is very small or zero.

[0003] The active material layer of the electrode of a semi-solid battery or a fully solid battery is assumed to contain a solid electrolyte in addition to the active material, conductive additive, and binder constituting the electrode active material layer of a conventional secondary battery. However, in batteries using electrodes containing solid electrolytes, the cycle characteristics are insufficient and there are problems in durability.

[0004] On the other hand, for example, Patent Document 1 discloses a method of using powder containing a specific element as a positive electrode conductive auxiliary agent, and Patent Document 2 discloses a method of coating a positive electrode active material and a conductive auxiliary agent.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-084496

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-055926 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, even in the solid-state batteries using the positive electrodes disclosed in Patent Documents 1 and 2, it cannot be said that the cycle characteristics are sufficiently improved, and a solid-state battery having excellent cycle characteristics is desired.

[0011] The present invention is accomplished in view of the above-mentioned problems, and its object is to provide a positive electrode active material layer capable of forming an all-solid-state battery with excellent cycle characteristics, an electrode having the positive electrode active material layer, and a semi-solid-state battery or an all-solid-state battery having the electrode.

[0012] Technical Solution

[0013] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by including a specific vinylidene fluoride copolymer as a binder in a positive electrode active material layer containing a positive electrode active material and a solid electrolyte, thereby completing the present invention.

[0014] The embodiment of the present invention relates to the following positive electrode active material layer, electrode, and semi-solid-state battery or all-solid-state battery, which contain a positive electrode active material (A), a solid electrolyte (B), and a binder (C).

[0015] [1] A positive electrode active material layer comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein the binder (C) comprises a vinylidene fluoride copolymer, which is a copolymer of vinylidene fluoride and hexafluoropropylene, or a copolymer of vinylidene fluoride and chlorotrifluoroethylene, and contains 83.0% by mass or more and 97.0% by mass or less of the structural units derived from vinylidene fluoride when all structural units of the vinylidene fluoride copolymer are set to 100.0% by mass.

[0016] [2] The positive electrode active material layer according to [1], wherein the intrinsic viscosity of the vinylidene fluoride copolymer is 1.5 dL / g or more.

[0017] [3] The positive electrode active material layer according to [2], wherein the intrinsic viscosity of the vinylidene fluoride copolymer is 2.4 dL / g or less.

[0018] [4] The positive electrode active material layer according to any one of [1] to [3], wherein the solid electrolyte (B) is an oxide-based solid electrolyte.

[0019] [5] The positive electrode active material layer according to [4], wherein the solid electrolyte (B) contains a material represented by the following formula (1).

[0020] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 ……(1)

[0021] (In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1).

[0022] [6] The positive electrode active material layer according to any one of [1] to [5], wherein the positive electrode active material (A) contains lithium metal phosphate, and the lithium metal phosphate is selected from the group consisting of LiFePO4, LiMnPO4, LiCoPO4 and LiNiPO4.

[0023] [7] An electrode comprising a current collector and the positive electrode active material layer according to any one of [1] to [6].

[0024] [8] A semi-solid-state battery or an all-solid-state battery comprising the electrode described in [7].

[0025] Beneficial Effects

[0026] According to the present invention, there can be provided a positive electrode active material layer capable of forming a semi-solid battery or an all-solid battery having excellent cycle characteristics, an electrode having the positive electrode active material layer, and a semi-solid battery or an all-solid battery having the electrode. DETAILED DESCRIPTION

[0027] 《Positive electrode active material layer》

[0028] The positive electrode active material layer contains a positive electrode active material (A), a solid electrolyte (B) and a binder (C).

[0029] The binder (C) contains a vinylidene fluoride copolymer.

[0030] The vinylidene fluoride copolymer is a copolymer of vinylidene fluoride and hexafluoropropylene, or a copolymer of vinylidene fluoride and chlorotrifluoroethylene.

[0031] The content of the structural unit derived from vinylidene fluoride in the copolymer is within a specific range as described below.

[0032] By containing the specific binder (C), the positive electrode active material layer can form a semi-solid battery or an all-solid battery having excellent cycle characteristics.

[0033] Hereinafter, essential or optional components contained in the positive electrode active material layer will be described.

[0034] <Positive Electrode Active Material (A)>

[0035] The positive electrode active material (A) is not particularly limited, and for example, a conventionally known positive electrode active material can be used. As the positive electrode active material, a lithium-based positive electrode active material containing at least lithium is preferred. Examples of the lithium-based positive electrode active material include: x M y O z(M is a transition metal element, x = 0.02 to 2.2, y = 1 to 2, z = 1.4 to 4) is a positive electrode active material. In the above general formula, M can be at least one selected from the group consisting of Co, Mn, Ni, V, Fe and Si, or at least one selected from the group consisting of Co, Ni and Mn. As such positive electrode active materials, specifically, LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2、LiMn2O4、Li(Ni 0.5 Mn 1.5 )O4, Li2FeSiO4, Li2MnSiO4, etc.

[0036] In addition, as the above general formula Li x M y O z The positive electrode active material (A) other than lithium titanate (e.g. Li4Ti5O 12 ), lithium metal phosphate (LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4), transition metal oxides (V2O5, MoO3), TiS2, LiCoN, Si, SiO2, Li2SiO3, Li4SiO4 and lithium storage metal compounds (such as Mg2Sn, Mg2Ge, Mg2Sb, Cu3Sb), etc. Among them, lithium metal phosphate is preferred, and among lithium metal phosphate, LiFePO4 is preferred.

[0037] The shape of the positive electrode active material (A) is not particularly limited, and may be, for example, a particle shape or a thin film shape. From the viewpoint of good handling properties, the positive electrode active material (A) may be a particle shape.

[0038] When the positive electrode active material is in the form of particles, the average particle size (D50) of the particles is, for example, preferably 1 nm or more and 100 μm or less, and more preferably 10 nm or more and 30 μm or less.

[0039] From the viewpoint of suppressing the reaction between the positive electrode active material and the solid electrolyte, a coating layer containing a Li ion conductive oxide may be formed on the surface of the positive electrode active material (A).

[0040] Examples of Li ion conductive oxides include LiNbO3, Li4Ti5O 12 And Li3PO4, etc.

[0041] The lower limit of the thickness of the coating layer is preferably 0.1 nm or more, and more preferably 1 nm or more. The upper limit of the thickness of the coating layer is preferably 100 nm or less, and more preferably 20 nm or less.

[0042] The content of the positive electrode active material (A) is not particularly limited, but is preferably 50% by mass or more and 98% by mass or less, more preferably 60% by mass or more and 95% by mass or less, and further preferably 70% by mass or more and 90% by mass or less, relative to 100% by mass of the positive electrode active material layer.

[0043] <Solid Electrolyte (B)>

[0044] As the solid electrolyte (B), a sulfide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used. Among them, an oxide-based solid electrolyte is preferably used from the viewpoint of safety and stability of the electrolyte.

[0045] As sulfide-based solid electrolytes, for example, there can be listed: Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5 and Li3PS4.

[0046] Examples of oxide-based solid electrolytes include LLTO-based compounds ((La, Li)TiO3), Li6La2CaTa2O 12 、Li6La2ANb2O 12 (A: alkaline earth metal), Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds (Li 1+x Al x Ge 2-x (PO4)3(0≤x≤1)), Li2O-Al2O3-TiO2-P2O5 and other LATP compounds (Li 1+ x Al x Ti 2-x (PO4)3(0≤x≤1))、Li 1+x Ti 2-x Al x Si y (PO4) 3-y (0≤x≤1,0≤y≤1), Li 1+y Al x M 2-x (PO4)3 (M is one or more elements selected from the group consisting of Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1), LiTi x Zr 2-x(PO4)3(0≤x≤1), LISICON(Li 4-2x Zn x GeO4(0≤x≤1)), LIPON compounds (Li 3+ y PO 4-x N x (0≤x≤1, 0≤y≤1)), NASICON compounds (LiTi2(PO4)3, etc.), garnet compounds (Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 (0≤x≤1) etc.

[0047] Among oxide-based solid electrolytes, LATP-based compounds are preferred from the viewpoint of having high lithium ion conductivity. As the LATP-based compound, a LATP-based compound containing a material represented by the following formula (1) is preferred.

[0048] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 ……(1)

[0049] (In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1).

[0050] In addition, as preferred oxide-based solid electrolytes other than the above-mentioned LATP-based compounds, for example, Li7La3Zr2O 12 (LLZO), Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 (LLZTO), Li 0.33 La 0.56 TiO3(LLTO), Li 1.6 Al 0.6 Ge 1.4 (PO4)3(LAGP), etc.

[0051] The content of the solid electrolyte (B) is not particularly limited, but is preferably 1% by mass or more and 40% by mass or less, more preferably 2% by mass or more and 20% by mass or less, and further preferably 5% by mass or more and 15% by mass or less, relative to 100% by mass of the positive electrode active material layer.

[0052] <Binder (C)>

[0053] The binder (C) is a vinylidene fluoride copolymer.

[0054] The vinylidene fluoride copolymer is a copolymer of vinylidene fluoride and hexafluoropropylene (hereinafter sometimes referred to as “vinylidene fluoride copolymer (Ca)”) or a copolymer of vinylidene fluoride and chlorotrifluoroethylene (hereinafter sometimes referred to as “vinylidene fluoride copolymer (Cb)”).

[0055] The vinylidene fluoride copolymer (Ca) or the vinylidene fluoride copolymer (Cb) is used to form a semi-solid battery or an all-solid battery having excellent cycle characteristics.

[0056] In addition, below, when there is no need to particularly distinguish between the vinylidene fluoride copolymer (Ca) and the vinylidene fluoride copolymer (Cb), they will be described simply as “vinylidene fluoride copolymer”.

[0057] From the viewpoint of excellent cycle characteristics of semi-solid batteries or all-solid-state batteries, when all structural units of the vinylidene fluoride copolymer are set to 100.0 mass%, the content of structural units derived from vinylidene fluoride (VDF) in the vinylidene fluoride copolymer is 83.0 mass% or more and 97.0 mass% or less, preferably 90.0 mass% or more and 96.0 mass% or less, and more preferably 93.0 mass% or more and 95.0 mass% or less.

[0058] (vinylidene fluoride copolymer (Ca))

[0059] The vinylidene fluoride copolymer (Ca) may be a copolymer using only vinylidene fluoride (VDF) and hexafluoropropylene (HFP), or may be a copolymer of VDF and HFP with other monomers other than these monomers. As other monomers, from the viewpoint of excellent cycle characteristics of semi-solid batteries or all-solid batteries, for example, monomers with polar functional groups having hydrogen bonding properties are preferred, and monomers containing carboxyl groups are more preferred. Examples of carboxyl-containing monomers that can be copolymerized with vinylidene fluoride include unsaturated monobasic acids such as acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, and 2-carboxyethyl methacrylate; unsaturated dibasic acids such as maleic acid and citraconic acid; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; acryloxyethyl succinic acid, acryloxypropyl succinic acid, methacryloyloxyethyl succinic acid, and methacryloyloxypropyl succinic acid. (vinylidene fluoride copolymer (Cb))

[0060] Vinylidene fluoride copolymer (Cb) can be a copolymer using only vinylidene fluoride (VDF) and chlorotrifluoroethylene (CTFE), or a copolymer of VDF and CTFE with other monomers other than these monomers. As other monomers, from the viewpoint that semi-solid batteries or all-solid batteries have excellent cycle characteristics, for example, monomers with polar functional groups with hydrogen bonding properties are preferred, and monomers containing carboxyl groups are more preferred. Examples of carboxyl-containing monomers that can be copolymerized with vinylidene fluoride include unsaturated monobasic acids such as acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, and 2-carboxyethyl methacrylate; unsaturated dibasic acids such as maleic acid and citraconic acid; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; acryloyloxyethyl succinic acid, acryloyloxypropyl succinic acid, methacryloyloxyethyl succinic acid, and methacryloyloxypropyl succinic acid.

[0061] From the viewpoint of excellent cycle characteristics of a semi-solid battery or an all-solid battery, the lower limit of the intrinsic viscosity of the vinylidene fluoride copolymer is preferably 1.0 dL / g or more, more preferably 1.2 dL / g or more, and even more preferably 1.5 dL / g or more.

[0062] From the viewpoint of excellent cycle characteristics of a semi-solid battery or an all-solid battery, the upper limit of the intrinsic viscosity of the vinylidene fluoride copolymer is preferably 3.0 dL / g or less, more preferably 2.8 dL / g or less, and even more preferably 2.4 dL / g or less.

[0063] The content of the binder (C) is not particularly limited, but is preferably 1% by mass to 40% by mass, more preferably 2% by mass to 30% by mass, and further preferably 3% by mass to 20% by mass, relative to 100% by mass of the positive electrode active material layer.

[0064] (Method for producing adhesive (C))

[0065] The method for producing the binder (C) is not particularly limited, and is generally carried out by suspension polymerization, emulsion polymerization, solution polymerization, etc. From the viewpoint of ease of post-treatment, aqueous suspension polymerization and emulsion polymerization are preferred, and aqueous suspension polymerization is more preferred.

[0066] The aqueous suspension polymerization method is not particularly limited, and examples thereof include a method in which monomers used for polymerization are polymerized in an aqueous medium in the presence of a suspending agent, a polymerization initiator, a chain transfer agent, and the like.

[0067] The suspending agent is not particularly limited, and examples thereof include methylcellulose, methoxylated methylcellulose, propoxylated methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, polyvinyl alcohol, polyethylene oxide, gelatin, etc. The amount of the suspending agent used is not particularly limited, and for example, is preferably 0.005 parts by mass or more and 1.0 parts by mass or less, and more preferably 0.01 parts by mass or more and 0.4 parts by mass or less, relative to 100 parts by mass of all monomers used in the polymerization.

[0068] As polymerization initiator, it is not particularly limited, for example, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-n-heptafluoropropyl peroxydicarbonate, isobutyryl peroxide, di(chlorofluoroacyl) peroxide, di(perfluoroacyl) peroxide, and tert-butyl peroxypivalate etc. can be listed. The usage amount of polymerization initiator is not particularly limited, for example, relative to 100 mass parts of all monomers used in the polymerization, preferably more than 0.05 mass part and less than 5 mass parts, more preferably more than 0.15 mass part and less than 2 mass parts.

[0069] The chain transfer agent is not particularly limited, and examples thereof include ethyl acetate, propyl acetate, acetone, and diethyl carbonate.

[0070] In addition, the amount of monomers used in the polymerization is calculated as the mass ratio of the total monomers to water, which is usually 1:1 to 1:10, preferably 1:2 to 1:5. The polymerization conditions such as the polymerization temperature and polymerization time when performing suspension polymerization are not particularly limited, and for example, known polymerization conditions can be used. The polymerization temperature T can be appropriately selected based on the 10-hour half-life temperature T10 of the polymerization initiator, and is usually selected within the range of T10-25°C ≤ T ≤ T10 + 25°C. For example, the T10 of tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are 54.6°C and 40.5°C, respectively (refer to the product catalog of NOF Corporation). Therefore, when tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are used as polymerization initiators for polymerization, the polymerization temperature T is selected within the range of 29.6°C ≤ T ≤ 79.6°C and 15.5°C ≤ T ≤ 65.5°C, respectively. The polymerization time is not particularly limited, and if productivity, etc. are taken into consideration, it is preferably 1 to 24 hours.

[0071] <Other ingredients>

[0072] As long as the effect of the present invention is not impaired, the positive electrode active material layer may also contain components other than the above-mentioned positive electrode active material (A), solid electrolyte (B) and binder (C) (hereinafter also referred to as "other components"). As other components, all known additives can be used, for example, conductive additives, insulating inorganic fillers such as aluminum oxide, magnesium oxide, and silicon dioxide, insulating organic fillers such as polytetrafluoroethylene, polyimide, and polyacrylonitrile, plasticizers such as ethylene carbonate, propylene carbonate, and ethyl methyl carbonate, Li salts such as LiPF6, LiFSI, and LiTFSI, dispersants, flame retardants, and defoamers can be listed.

[0073] Examples of the conductive additive (D) include carbon black and carbon nanotubes, etc. These may be used alone or in combination of two or more.

[0074] The content of the conductive aid (D) is not particularly limited, but is preferably 0.05% by mass to 20% by mass, more preferably 0.1% by mass to 15% by mass, and further preferably 0.5% by mass to 10% by mass, relative to 100% by mass of the positive electrode active material layer.

[0075] "electrode"

[0076] The electrode is a positive electrode and includes a current collector and the positive electrode active material layer described above.

[0077] By providing the above-mentioned positive electrode active material layer, the electrode can be formed into a semi-solid battery or an all-solid battery having excellent cycle characteristics.

[0078] (Current Collector)

[0079] The current collector is a terminal for taking out electricity. The material of the current collector is not particularly limited, and metal foil or metal mesh of aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc. can be used. In addition, it can also be a material formed by applying the above-mentioned metal foil or metal mesh on the surface of other media.

[0080] The volume density of the electrode is not particularly limited, but is preferably 1.5 g / cm 3 Above and 5.0g / cm 3 the following.

[0081] The weight per unit area of ​​the electrode is not particularly limited, but is preferably 20 g / m 2 Above and 1000g / m 2 the following.

[0082] 《Electrode manufacturing method》

[0083] As a method for manufacturing an electrode, for example, there can be cited a method including the following steps: a step of mixing the above-mentioned positive electrode active material (A), solid electrolyte (B), binder (C), other components as required, and non-aqueous solvent (S) to prepare a positive electrode slurry; a step of applying the obtained positive electrode slurry to a collector and then drying it. That is, in the above-mentioned embodiment, after the step of drying the positive electrode slurry, the positive electrode active material layer is prepared, and the electrode is also prepared.

[0084] Examples of the non-aqueous solvent (S) include N-methyl-2-pyrrolidone (hereinafter referred to as "NMP"), dimethylformamide, N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, cyclohexanone, methyl ethyl ketone, and tetrahydrofuran. These may be used alone or in combination of two or more.

[0085] The coating method is not particularly limited, and for example, a doctor blade method, a reverse roll method, a comma bar method, a gravure printing method, an air knife method, a die coating method, a dip coating method, and the like can be applied.

[0086] The drying temperature is, for example, preferably 80° C. or higher and 300° C. or lower, more preferably 90° C. or higher and 200° C. or lower, and further preferably 100° C. or higher and 180° C. or lower.

[0087] The drying time is, for example, preferably 10 seconds to 300 minutes, more preferably 1 minute to 200 minutes.

[0088] Drying can be performed multiple times at different temperatures. During drying, pressure can be applied.

[0089] All-solid-state battery

[0090] The all-solid-state battery includes the electrode of the above-described embodiment. As the all-solid-state battery, conventionally known components can be used for components other than the positive electrode, such as the negative electrode and the separator.

[0091] Semi-solid-state battery

[0092] The semi-solid battery has the electrode of the above embodiment. As a semi-solid battery, parts other than the positive electrode, such as the negative electrode, the separator, etc., can use the parts known in the past. When the volume of the electrolyte contained in the conventional secondary battery is set to 100%, the amount of electrolyte contained in the semi-solid battery is preferably 1% to 95%, more preferably 5% to 90%, and further preferably 10% to 80%.

[0093] (Cycle Characteristics)

[0094] As for the cycle characteristics of the solid-state battery, constant current charging and discharging are carried out under the conditions of an ambient temperature of 25°C, a charge and discharge rate of 0.5C, and a voltage range of 2.5V to 4.0V. The discharge capacity after 50 cycles is preferably 140mAh / g or more, more preferably 145mAh / g or more, and further preferably 150mAh / g or more.

[0095] Example

[0096] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0097] [Examples 1 to 5 and Comparative Examples 1 to 6]

[0098] <Materials used>

[0099] In the examples and comparative examples, the following A1 was used as the positive electrode active material (A).

[0100] A1:LiFePO4.

[0101] In Examples and Comparative Examples, the following B1 was used as the solid electrolyte (B).

[0102] B1: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (LATP)(OHARA Corporation, "LICGC TM PW-01 (particle size 1 μm)”).

[0103] In the examples and comparative examples, the following C1 to C10 were prepared and used as the adhesive (C). In addition, the intrinsic viscosity of each prepared adhesive was measured by the following method.

[0104] (Determination of intrinsic viscosity)

[0105] 80 mg of each binder was dissolved in 20 ml of N,N-dimethylformamide to prepare a binder-containing solution. Then, the viscosity η1 of the binder-containing solution was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. Similarly, the viscosity η0 of N,N-dimethylformamide was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. Then, the intrinsic viscosity η was calculated based on the following formula.

[0106] Intrinsic viscosity η=(1 / C)·ln(η1 / η0)

[0107] In the above formula, C is the concentration of the solution containing the adhesive per unit, and C is 0.4 g / dl. (Preparation Example of Adhesive C1 (VDF / HFP))

[0108] 290 parts by mass of ion exchange water, 0.15 parts by mass of methylcellulose, 57.9 parts by mass of vinylidene fluoride (VDF), 7.8 parts by mass of hexafluoropropylene (HFP), and 0.9 parts by mass of diisopropyl peroxydicarbonate (IPP) were added to an autoclave with a volume of 2L, and polymerized at 45°C. 34.3 parts by mass of VDF were added to obtain a copolymer. After the obtained copolymer was heat-treated at 95°C for 60 minutes, it was dehydrated and washed with water, and then dried at 80°C for 20 hours to obtain an adhesive C1. In the adhesive C1, 94.3% by mass of VDF and 5.7% by mass of HFP were contained relative to all structural units. The intrinsic viscosity (η) of the adhesive C1 is 1.5dL / g.

[0109] (Preparation Example of Adhesive C2 (VDF / HFP))

[0110] Into a 2L autoclave were added 253.0 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 90.0 parts by mass of vinylidene fluoride (VDF), 10.0 parts by mass of hexafluoropropylene (HFP), 0.4 parts by mass of IPP, and 1.0 parts by mass of ethyl acetate, and polymerization was carried out at 45°C. After the obtained copolymer was heat-treated at 95°C for 60 minutes, it was dehydrated and washed with water, and then dried at 80°C for 20 hours to obtain Adhesive C2. In Adhesive C2, 93.0% by mass of VDF and 7.0% by mass of HFP are contained relative to all structural units. The intrinsic viscosity (η) of Adhesive C2 is 1.9dL / g. (Production Example of Adhesive C3 (VDF / HFP))

[0111] Adhesive C3 was obtained by polymerizing VDF and HFP in the same manner as Adhesive C2 except that 256.4 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 82.0 parts by mass of VDF, 18.0 parts by mass of HFP, 0.4 parts by mass of IPP, and 0.9 parts by mass of ethyl acetate were used. Adhesive C3 contained 85.0% by mass of VDF and 15.0% by mass of HFP relative to all structural units. The intrinsic viscosity (η) of Adhesive C3 was 1.8 dL / g.

[0112] (Production Example of Adhesive C4 (VDF / CTFE))

[0113] Adhesive C4 was obtained by polymerizing VDF and CTFE in the same manner as in the preparation example of Adhesive C2, except that 256.6 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 96.0 parts by mass of VDF, and 4.0 parts by mass of chlorotrifluoroethylene (CTFE) were used instead of HFP, 0.6 parts by mass of IPP, and 0.59 parts by mass of ethyl acetate. Adhesive C4 contained 96.0% by mass of VDF and 4.0% by mass of CTFE relative to all structural units. The intrinsic viscosity (η) of Adhesive C4 was 2.1 dL / g.

[0114] (Preparation Example of Adhesive C5 (VDF / HFP / MMM))

[0115] Adhesive C5 was obtained by polymerizing VDF, HFP and MMM in the same manner as in the preparation example of adhesive C2 except that 259 parts by mass of ion exchange water, 0.15 parts by mass of methylcellulose, 90.0 parts by mass of VDF, 10.0 parts by mass of HFP, 0.5 parts by mass of monomethyl maleate (MMM) and 0.5 parts by mass of IPP were used. It should be noted that the amount of each monomer in adhesive C5 was determined as follows: the VDF / HFP ratio was calculated using 19F-NMR, the VDF / MMM ratio was determined using the following method, and then the total of VDF, HFP and MMM was calculated to be 100 mol%.

[0116] The VDF / MMM ratio (the molar ratio of the amount of structural units derived from vinylidene fluoride to the amount of structural units derived from monomethyl maleate) in the copolymer was calculated based on the calculation method using the IR spectrum and the standard curve disclosed in International Publication No. 2009 / 084483. In the adhesive C5, 92.5% by mass of VDF, 7.0% by mass of HFP, and 0.5% by mass of MMM were contained relative to all structural units. The intrinsic viscosity (η) of the adhesive C5 was 2.6 dL / g.

[0117] (Preparation Example of Adhesive C6 (PVDF))

[0118] Adhesive C6, which is a homopolymer of VDF, was obtained by polymerizing VDF in the same manner as in the preparation example of Adhesive C2 except that 231.8 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 100 parts by mass of VDF, 0.7 parts by mass of IPP, and 0.7 parts by mass of ethyl acetate were used. Adhesive C6 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of Adhesive C6 was 2.1 dL / g.

[0119] (Preparation Example of Adhesive C7 (PVDF))

[0120] Adhesive C7, which is a homopolymer of VDF, was obtained by polymerizing VDF in the same manner as in the preparation example of Adhesive C2 except that 213.8 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 100 parts by mass of VDF, 0.3 parts by mass of IPP, and 0.4 parts by mass of ethyl acetate were used. Adhesive C7 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of Adhesive C7 was 3.1 dL / g.

[0121] (Production Example of Adhesive C8 (VDF / HFP / MMM))

[0122] Adhesive C8 was obtained by polymerizing VDF, HFP and MMM in the same manner as in the preparation example of adhesive C2 except that 240.2 parts by mass of ion exchange water, 0.2 parts by mass of methylcellulose, 96.7 parts by mass of VDF, 3.0 parts by mass of HFP, 0.3 parts by mass of MMM and 0.47 parts by mass of IPP were used. Adhesive C8 contained 97.4% by mass of VDF, 2.3% by mass of HFP and 0.3% by mass of MMM relative to all structural units. The intrinsic viscosity (η) of adhesive C8 was 3.1 dL / g.

[0123] (Preparation Example of Adhesive C9 (VDF / TFE))

[0124] With reference to Japanese Patent No. 5949915, VDF and TFE were polymerized to obtain Adhesive C9. Adhesive C9 contained 78.0% by mass of VDF and 22.0% by mass of TFE relative to all structural units. The intrinsic viscosity (η) of Adhesive C9 was 2.4 dL / g.

[0125] (Production Example of Adhesive C10 (VDF / TFE))

[0126] With reference to Japanese Patent No. 5949915, VDF and TFE were polymerized to obtain Adhesive C10. Adhesive C10 contained 86.8% by mass of VDF and 13.2% by mass of TFE relative to all structural units. The intrinsic viscosity (η) of Adhesive C9 was 2.3 dL / g.

[0127] (Production Example of Adhesive C11 (VDF / HFP))

[0128] Adhesive C11 was obtained by polymerizing VDF and HFP in the same manner as in the preparation example of adhesive C2, except that 258.0 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 75 parts by mass of VDF, 25 parts by mass of HFP, and 0.7 parts by mass of IPP were used. Adhesive C11 contained 81.2% by mass of VDF and 18.8% by mass of HFP relative to all structural units. The intrinsic viscosity (η) of adhesive C11 was 1.6 dL / g.

[0129] Table 1 shows the detailed information of the obtained adhesives C1 to C11.

[0130] [Table 1]

[0131]

[0132]

[0133] In Examples and Comparative Examples, D1 described below was used as the conductive auxiliary agent (D).

[0134] D1: Carbon nanotube (CNT) dispersion.

[0135] In Examples and Comparative Examples, S1 described below was used as the nonaqueous solvent (S).

[0136] S1: N-methyl-2-pyrrolidone (NMP).

[0137] (Preparation of positive electrode slurry)

[0138] Each binder (C) is dispersed in N-methyl-2-pyrrolidone (NMP) at room temperature so that the concentration of the binder (C) becomes an arbitrary concentration, and then the solution temperature is raised to 50°C to dissolve each binder (C) (hereinafter referred to as "binder solution"). Using a positive electrode active material (A), a solid electrolyte (B), a conductive aid (D) and each of the above-mentioned binder solutions, each component is mixed in a manner of positive electrode active material (A) / solid electrolyte (B) / conductive aid (D) / binder (C) = 90 / 10 / 2 / 10 (mass %) to obtain each positive electrode slurry. The solid content of the positive electrode slurry is adjusted using NMP.

[0139] (Fabrication of positive electrode)

[0140] Each of the obtained positive electrode slurries was applied to an Al foil (thickness 15 μm), and then dried at 120° C. Each of the obtained preliminary positive electrodes was pressed and further heat treated at 120° C. for 3 hours. Thus, an electrode volume density of 2.3 g / cm 3 , weight per unit area is 200g / m 2 of each positive electrode.

[0141] (Test battery cell production)

[0142] Each positive electrode obtained was punched into Φ14 mm, and a 2016-size button battery unit was produced using metal Li as a counter electrode and a PE single-layer separator (thickness 20 μm) as a separator. It should be noted that the electrolyte used was a solution containing 1.2 M LiPF6 (1 mass % of vinylene carbonate (VC)) in a mixed solution of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC / EMC=3 / 7 (volume ratio)).

[0143] <Evaluation>

[0144] The charge and discharge characteristics of each of the obtained test battery cells were measured by the following method.

[0145] (Cycle Characteristics)

[0146] Each test battery cell was subjected to CCCV charge / CC discharge at an ambient temperature of 25°C, a charge and discharge rate of 0.5C, a voltage range of 2.5V to 4.0V, and a CCCV charge termination current value of 0.05C, and the discharge capacity after 50 cycles was measured. The results are shown in Table 2.

[0147] [Table 2]

[0148]

[0149] As can be seen from Table 2, in the positive electrode active material layers of Comparative Examples 1 and 2 using a homopolymer of VDF as the binder (C), the maximum discharge capacity after 50 cycles was only 123.7 mAh / g.

[0150] In addition, in the positive electrode active material layer of Comparative Examples 4 to 5 using a copolymer of VDF and TFE as a binder (C), the discharge capacity after 50 cycles was less than 140 mAh / g. Similarly, in the positive electrode active material layer of Comparative Example 3 using a copolymer of VDF and HFP and a copolymer containing more than 97.0% by mass of structural units derived from VDF as a binder (C), the discharge capacity after 50 cycles was less than 140 mAh / g.

[0151] In the positive electrode active material layer of Comparative Example 6 using a copolymer of VDF and HFP in which the structural unit derived from VDF was less than 83% by mass as the binder (C), the discharge capacity after 50 cycles was less than 140 mAh / g.

[0152] On the other hand, in the positive electrode active material layer using a copolymer of VDF and HFP, and a copolymer of VDF and CTFE in which the structural unit derived from VDF is 83.0 mass % or more and 97.0 mass % or less as a binder (C), as shown in Examples 1 to 5, the discharge capacity after 50 cycles is 140 mAh / g or more, which shows that it has excellent cycle characteristics.

Claims

1. A positive electrode active material layer, comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein: The binder (C) contains a vinylidene fluoride copolymer, The vinylidene fluoride copolymer is a copolymer of vinylidene fluoride and hexafluoropropylene, or a copolymer of vinylidene fluoride and chlorotrifluoroethylene. When all the structural units of the vinylidene fluoride copolymer are taken as 100.0 mass %, the structural units derived from vinylidene fluoride are contained in an amount of 83.0 mass % to 97.0 mass %.

2. The positive electrode active material layer according to claim 1, wherein The intrinsic viscosity of the vinylidene fluoride copolymer is 1.5 dL / g or more.

3. The positive electrode active material layer according to claim 2, wherein The intrinsic viscosity of the vinylidene fluoride copolymer is 2.4 dL / g or less.

4. The positive electrode active material layer according to any one of claims 1 to 3, wherein The solid electrolyte (B) is an oxide-based solid electrolyte.

5. The positive electrode active material layer according to claim 4, wherein The solid electrolyte (B) comprises a material represented by the following formula (1): There 1+x+y To the x You 2-x Yes y P 3-y OR 12 ……(1) In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1.

6. The positive electrode active material layer according to any one of claims 1 to 3, wherein The positive electrode active material (A) contains lithium metal phosphate, The lithium metal phosphate is selected from the group consisting of LiFePO 4 , LiMnPO 4 , LiCoPO 4 and LiNiPO 4 . 7 . An electrode comprising a current collector and the positive electrode active material layer according to claim 1 .

8. A semi-solid-state battery or an all-solid-state battery, comprising the electrode according to claim 7.

Citation Information

Patent Citations

  • Method and apparatus for controlling mold temperature

    JP1984049915A

  • Positive electrode for all-solid battery, and all-solid battery including the positive electrode

    JP2013084496A

  • Sulfide solid battery

    JP2018055926A